ANALISIS DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA RUMAH SAKIT SANTA ELISABETH MEDAN - Simanihuruk, Peran; Tamba, Darwis; Sipahutar, Robinson; Parhusip, Poltak T.; Sitorus, Putri Dwi Ana (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This research aims to examine the influence of service quality dimensions, including reliability, responsiveness, assurance, tangibles, and empathy, on patient satisfaction at Santa Elisabeth Hospital in Medan. The study sample consists of 96 patients, with data collected through questionnaires and documentation. Data analysis was conducted using descriptive and inductive methods. The results indicate that reliability, responsiveness, assurance, tangibles, and empathy positively affect patient satisfaction, with assurance having a greater impact on patient satisfaction compared to reliability, responsiveness, tangibles, and empathy. Both t-tests and F-tests show that reliability, responsiveness, assurance, tangibles, and empathy have a positive and significant partial and simultaneous effect on patient satisfaction at Santa Elisabeth Hospital in Medan. The coefficient of determination (R Square) value is 0.514, indicating that 51.4% of patient satisfaction can be explained by the service quality dimensions (reliability, responsiveness, assurance, tangibles, and empathy), while the remaining 48.6% is explained by other factors not covered in this study, such as security, promotion, and communication. To enhance the service quality dimensions related to reliability, responsiveness, assurance, tangibles, and empathy, continuous improvements are necessary to increase patient satisfaction.